2020
DOI: 10.1038/s41467-020-15071-9
|View full text |Cite
|
Sign up to set email alerts
|

The substrate specificity switch FlhB assembles onto the export gate to regulate type three secretion

Abstract: Protein secretion through type-three secretion systems (T3SS) is critical for motility and virulence of many bacteria. Proteins are transported through an export gate containing three proteins (FliPQR in flagella, SctRST in virulence systems). A fourth essential T3SS protein (FlhB/SctU) functions to "switch" secretion substrate specificity once the growing hook/ needle reach their determined length. Here, we present the cryo-electron microscopy structure of an export gate containing the switch protein from a V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
96
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(100 citation statements)
references
References 48 publications
(69 reference statements)
3
96
0
Order By: Relevance
“…FliR (10 subunits) and FliP 5 FliQ 4 FliR 1 FlhB 1 (11 subunits) complexes19,30 , and the helical parameter is similar to those of the flagellar axial structures, such as the rod, hook and filament, with about 5.5 subunits per turn of the 1-start helix, which can also be regarded as a tubular structure with 11 protofilaments. However, the 11-fold symmetry feature of the internal part of the M ring is not the one directly associated with the export gate at the center of the M ring.…”
mentioning
confidence: 95%
“…FliR (10 subunits) and FliP 5 FliQ 4 FliR 1 FlhB 1 (11 subunits) complexes19,30 , and the helical parameter is similar to those of the flagellar axial structures, such as the rod, hook and filament, with about 5.5 subunits per turn of the 1-start helix, which can also be regarded as a tubular structure with 11 protofilaments. However, the 11-fold symmetry feature of the internal part of the M ring is not the one directly associated with the export gate at the center of the M ring.…”
mentioning
confidence: 95%
“…FliP, FliQ and FliR form a polypeptide channel complex for the translocation of export substrates across the cytoplasmic membrane 6,7 . FlhB associates with the FliP/FliQ/FliR complex and is postulated to coordinate gate opening of the polypeptide channel 8 . FlhA associates not only with the FliP/FliQ/FliR complex but also with the MS ring 9 .…”
mentioning
confidence: 99%
“…Our initial results suggested that the length of the amino acid side chain was important for the function of the M-gasket. Thereafter, several structural studies have confirmed that the M-loop is indeed exposed to the channel in both fT3SS and vT3SS (8)(9)(10). In the FliPQR secretion pore, five copies of FliP are present, which results in a local pool of 15 methionine residues that are spread over about 20Å at the base of the channel (Figure 2A).…”
Section: The Methionine Loop In Flip Regulates Membrane Gatingmentioning
confidence: 89%